Optimization Study of Water Allocation in Turus Irrigation Area Using Dynamic Programming Approach - Susanto, Rizki Heru; Purnomo, Dimas Aji; Sujatmiko, Heri (Jurnal Teknik Sipil, 2025)
The irrigation system is one of the key factors influencing agricultural land productivity, particularly in rice fields. Proper and efficient water resource management is a crucial strategy to enhance agricultural production efficiency. The Turus irrigation area, covering 424 hectares, frequently faces challenges in water distribution due to both oversupply and inaccuracies in determining cropping patterns. This study aims to optimize irrigation water allocation in the area to achieve maximum agricultural output. The optimization process involves comparing the water requirements for specific crops with the available water supply to determine the most beneficial allocation. The results show that the water requirement during the second dry season planting period (MK II), from July to October, reaches 5.405,59 m ³/ha. Based on the water balance analysis and limited water availability, the optimization is focused on rice and secondary crops during the MK II season. Through a dynamic programming approach, an optimal water allocation was achieved, successfully irrigating the entire 424-hectare area and yielding a maximum profit of IDR 6.538.080.000,00. These findings demonstrate that optimizing water allocation using the dynamic programming method is a strategic approach to improving the efficiency and productivity of the irrigation system.